Innovating TRoW as workforce game-based learning for sustainable education - Abd Rahman, Nurul Hayani; Shafie, Nani Ilyana; Ismail, Shaira; Abd Rahman, Nurul Fazila (2025)
Tactic Rush Workforce (TRoW) is a board game developed to simulate real-world human resource (HR) challenges and sustainable education in higher education. As a physical and interactive educational learning tool, TRoW engages students in workplace scenarios that require them to manage key HR functions, including recruitment, skill matching, workforce development, compensation planning, and strategic decision-making. The game employs experiential learning to help students explore essential HR practices and understand current labor market trends. Unlike digital simulations, TRoW is expected to encourage active, in-person participation, fostering collaboration, critical thinking, communication, and competencies vital to academic success and career readiness. Its design enhances both cognitive and social engagement, prompting students to reflect on policies, sustainability goals, and long-term planning in workforce management. This idea generation aligns with sustainable education principles by requiring players to consider the environmental, social, and economic implications of their decisions. This integration supports the development of well-rounded, future-ready skills consistent with the United Nations Sustainable Development Goals (SDGs). By combining game-based learning with strategic thinking and sustainability awareness, TRoW is introduced as a potential educational tool. It will prepare students not only for employment but also for responsible decision-making in complex, real-world contexts. This paper explores the game's design and potential to cultivate workforce competencies for various jobs available in different industries.